THE INFLUENCE OF SOCIOECONOMIC STATUS ON EARLY CHILDHOOD PROSOCIAL BEHAVIOUR IN EAST LAMPUNG REGENCY, LAMPUNG PROVINCE - suryadi suryadi; Nurbiana Dhineni; Edwita Edwita (Universitas Panca Sakti Bekasi, 2024)
Abstract: The aim of this research is to find out the socio-economic status of parents influenced or not influential on the prosocial behavior of children of school B in the district of East Lampung, Province of Lampung. This type of research is quantitative research, the population in this study is 250 parents and the sample study is 80 students and the sampling technique used is simple random samplings. The instrument used in this study is the questioner, the test of the hypothesis in the study is performed with simple linear regression analysis. The results of this study show that: (1) There is an impact of the socio-economic status of the parent on the child's social behaviour (2) Large The impact of a parent's socio - economic status on the aggressive behaviour of the child obtained from the R square value of 0.364 indicates that the social status of parents influences the children's prosocial behaviours by 36.6% and 63.4% is influenced by other factors. Keyword: socioeconomic status, prosocial behaviour, early childhood